Wave interference in railway track due to multiple wheels. (3rd March 2022) - Lei, Simian; Ge, Yaojun; Li, Qi; Thompson, David J.
Highlights: Reveal the nature of the boundary conditions provided by wheels mounted on the track. Explain the generation of multiple peaks in track vibration based on phase closure. Explain the highest response peak around 700 Hz due to total reflection at the wheels. Abstract: A resonance pattern at frequencies from around 400 Hz to 1000 Hz has often been observed from measured rail accelerations. Such resonances are important for rail noise and corrugation. Although this pattern has been reported and discussed in several papers in terms of wave reflections between multiple wheels, the aim of this study is to investigate the generation mechanism of this resonance phenomenon in detail, and to give both mathematical and physical insight. An infinite Timoshenko beam with continuous supports is adopted for modeling the track system, and the point and transfer receptances of the rail for a stationary harmonic excitation are explicitly obtained by the residue theorem. A frequency-domain method is then presented to calculate the power spectral densities of the wheel-track coupled system responses to stochastic irregularities with the moving irregularity model. It is found that the multiple peaks can be explained by using the phase closure principle. Moreover, total reflection between the two wheels may occur at around 700 Hz, which results in the highest peak in the response.